2018
DOI: 10.5897/err2017.3429
|View full text |Cite
|
Sign up to set email alerts
|

Primary school students views about science, technology and engineering

Abstract: Some of the main goals of science education are to increase students" knowledge about the technology and engineering design process, and to train students as scientifically and technologically literate individuals. The main purpose of this study is to find out primary students" views about science, technology and engineering. For this aim and in order to increase students" knowledge and understanding of science, technology and engineering, a module named "Engineering and Technology Lessons for Children" develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Studies employing the Draw-an-Engineer (DAE) instrument (Knight& Cunningham, 2004) highlight the stereotypical misconceptions that children hold about engineering. Children often perceive engineers as people who build and fix things and are much more likely to create drawings of white, male engineers who are working alone than drawings of women, minorities, or people working in groups (Pekmez, 2018;Newley, Kaya, Yesilyurt, & Deniz, 2017;Hammack and High, 2014;Karatas, Micklos, & Bodner, 2011;Fralick, Kearn, Thompson, & Lyons, 2009).…”
Section: Perceptions Of Engineersmentioning
confidence: 99%
“…Studies employing the Draw-an-Engineer (DAE) instrument (Knight& Cunningham, 2004) highlight the stereotypical misconceptions that children hold about engineering. Children often perceive engineers as people who build and fix things and are much more likely to create drawings of white, male engineers who are working alone than drawings of women, minorities, or people working in groups (Pekmez, 2018;Newley, Kaya, Yesilyurt, & Deniz, 2017;Hammack and High, 2014;Karatas, Micklos, & Bodner, 2011;Fralick, Kearn, Thompson, & Lyons, 2009).…”
Section: Perceptions Of Engineersmentioning
confidence: 99%
“…We conducted interviews because these allow students to better express a deeper level of their conceptual understanding of science than writing instruments (Kilinc et al 2013;Tomas and Ritchie 2015). This is especially true for elementary school students who generally have greater difficulty expressing themselves in writing than orally (Angeloudi, Papageorgiou, and Markos 2018;Pekmez 2018). We opted for individual interviews because we wanted to understand the impacts of learning about living organisms for each student without peer influence during data collection.…”
Section: Data Collectionmentioning
confidence: 99%
“…Individuals' drawings have long been used as a form of assessment of mental images ranging from the Draw-A-Man test (Goodenough, 1926) to the Draw-A-Scientist test (Chambers, 1983;Mason et al, 1991) and, more recently, the Draw-An-Engineer test (DAET) (Knight & Cunningham, 2004). Studies using DAET highlight stereotypical misconceptions that children hold of engineers, such as people who build and fix things, as well as the tendency to include images of white, male engineers who are working alone more often than drawings of women, minorities, or people working in groups (Capobianco et al, 2011;Fralick et al, 2009;Karatas et al, 2011;Newley et al, 2017;Pekmez, 2018). In a study of middle school girls who had participated in an after-school engineering mentoring program, Hammack and High (2014) found that participants were more likely to draw female engineers.…”
Section: Draw-an-engineer Testmentioning
confidence: 99%